The process of multiplying complex numbers is very similar when we multiply two binomials.
The only difference is the introduction of the expression:
![\sqrt[]{-1}\text{ = i}](https://img.qammunity.org/2023/formulas/mathematics/college/ejx6b2k3yrvz8jlz9b9ijvvldmff8rtby5.png)
For example,
Multiply 2i by 8i
![\begin{gathered} 2i\text{ }*\text{ 8i = 2}*\text{ 8}*\text{ i}*\text{ i} \\ =\text{ 16}* i^2 \\ =\text{ 16 }*\text{ -1} \\ =\text{ -}16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/638w63iklz0wmdj2qyrp0fxceosms7ebbo.png)
We must remember the following when multiplying imaginary numbers:
![\begin{gathered} \sqrt[]{-1}\text{ = i} \\ i^2\text{ = -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u3gjl8gbnj4l62zu6jl1db5d5qg05eo7vu.png)
Let's work on another example:
(2i)^4:
![\begin{gathered} =(2i)^4 \\ =\text{ 2i }*\text{ 2i }*\text{ 2i }*\text{ 2i} \\ =\text{ 2}*2*2*2\text{ }* i* i* i* i \\ =\text{ 16 }* i^2\text{ }* i^2 \\ =\text{ 16 }*\text{ -1}*-1 \\ =\text{ 16} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/68walud46ib89jl9r83h0cawycuasqw1xn.png)
Remember that:
![\begin{gathered} i^2\text{ = -1} \\ i^3=i^2\text{ }*\text{ i} \\ =\text{ -i} \\ i^4=i^2\text{ }* i^2 \\ =\text{ -1 }*\text{ -1} \\ =\text{ 1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vlsw35dbp1uh3xmq4zazywshjlfhqoa5v4.png)
Anytime we raise i to any power, the result changes depending on the value of the power. We can obtain the result by evaluating the terms as shown above.